2019
DOI: 10.1002/med.21576
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the riboflavin biosynthesis pathway for the development of antimicrobial agents

Abstract: Life on earth depends on the biosynthesis of riboflavin, which plays a vital role in biological electron transport processes. Higher mammals obtain riboflavin from dietary sources; however, various microorganisms, including Gram‐negative pathogenic bacteria and yeast, lack an efficient riboflavin‐uptake system and are dependent on endogenous riboflavin biosynthesis. Consequently, the inhibition of enzymes in the riboflavin biosynthesis pathway would allow selective toxicity to a pathogen and not the host. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 113 publications
(234 reference statements)
0
9
0
Order By: Relevance
“…Therapeutic targeting of IL-17 is hypothesised to inhibit development of ARDS [ 98 ]. It is possible that MAIT cell functions could also be therapeutically inhibited using inhibitory riboflavin biosynthesis pathway derivatives [ 99 ]. However, given the observed importance of MAIT cell activation in promoting effector T cell vaccine responses and promoting vaccine immunogenicity, it may not be advisable to completely inhibit MAIT cell activation in this setting.…”
Section: Therapeutic Potential Of Unconventional T Cells In Covid-19mentioning
confidence: 99%
“…Therapeutic targeting of IL-17 is hypothesised to inhibit development of ARDS [ 98 ]. It is possible that MAIT cell functions could also be therapeutically inhibited using inhibitory riboflavin biosynthesis pathway derivatives [ 99 ]. However, given the observed importance of MAIT cell activation in promoting effector T cell vaccine responses and promoting vaccine immunogenicity, it may not be advisable to completely inhibit MAIT cell activation in this setting.…”
Section: Therapeutic Potential Of Unconventional T Cells In Covid-19mentioning
confidence: 99%
“…Indeed, an immunomodulatory strategy of herpesviruses that functionally disrupts the immune response was defined for MR1 targeting ( 14 ). It was found that riboflavin biosynthesis can be repressed by inhibiting enzymes involved in riboflavin biosynthesis ( 15 ) or at the level of transcription through the flavin mononucleotide (FMN) riboswitch ( 16 ). The FMN riboswitch is a metabolite-dependent RNA element that directly binds FMN and controls the expression of genes responsible for riboflavin biosynthesis since FMN is riboflavin-5′-phosphate ( 17 ).…”
Section: Inhibition Of Riboflavin Biosynthesis In Microbiota As a Posmentioning
confidence: 99%
“…In this case, glucose and mannose feed the glycolysis while xylose feeds the PPP, avoiding metabolic burden and reaching the riboflavin titer of 11.7 mg L −1 , the highest titer up to this point of this work (Figure 3C). Ribulose-5-phosphate is a metabolite of the PPP [49], but also it is the initial precursor for riboflavin biosynthesis [50]. When using the oxidoreductase pathway for xylose consumption, the organism generates xylulose-5-phosphate.…”
Section: Discussionmentioning
confidence: 99%